THE EFFECT OF Anredera cordifolia (Ten.) Steenis SUPPLEMENTATION ON UTERINE INVOLUTION PROCESS EVALUATED BY OESTRUS POST PARTUM BEHAVIOR AND FERNING - Purwasih, R.; Setiatin, E.T.; Samsudewa, D. (Diponegoro University, 2014)
The aim of this study was to determine the effect of Anrederacordifolia (Ten.) Steenissupplementation on uterine involution process in rabbit. The research design applied was completelyrandomized design with 4 treatments and 3 replications (T0 = without Anredera cordifoliasupplementation; TI = Anredera cordifolia supplemented two days before parturition; T2 = Anrederacordifolia supplemented two days after parturition; T3 = Anredera cordifolia supplemented two daysbefore until two days after parturition). The results showed that Anredera cordifolia (Ten.) Steenissupplementation could accelerate post partum oestrus in does that were characterized by post partumoestrus behavior, ferning of saliva and cervical mucus. The best treatment was T3, that was four daysAnredera cordifolia supplementation that was administered at 0.45 g/kg of body weight/day. Furtherresearch was needed to find an optimal dose of Anredera cordifolia (Ten.) Steenis on uterine involution.